African crossroads : intersections between history and anthropology in Cameroon - Fowler, Ian; Zeitlyn, David (Cameroon studies ;, 1996)
Cameroon is characterized by an extraordinary geographical, cultural, and linguistic diversity. This collection of essays by eminent historians and anthropologists summarizes three generations of research in Cameroon that began with the collaboration of Phyllis Kaberry and E. M. Chilver soon after the Second World War and continues to this day. The idea for this book arose from a concern to recognize the continuing influence of E. M. Chilver on a wide variety of social, historical, political and economic studies. The result is a volume with a broad historical scope yet one that also focuses on major contemporary theoretical issues such as the meaning and construction of ethnic identities and the anthropological study of historical processes. For more information on this title and related publications, go to http://lucy.ukc.ac.uk/Chilver/index.html.